Use of the Jeffersons Medical Empathy Scale in Resident physicians in specialization training in a Peruvian hospital. - Mayo, Gualber V. (2019)
Empathy is defined as the ability to understand the feelings and emotions of others, based on the recognition of the other as similar. Applied to the doctor-patient relationship can improve clinical outcomes, reason for which it is considered an essential ability in the training of every medical professional. Objective: To identify the level of empathy and related factors in resident physicians in medical and surgical specialized training in a hospital in Lima, Peru. Material and methods: Sociodemographic, personal and professional data were obtained and the Jefferson Medical Empathy Scale, consisting of 20 questions and a 1 to 7 Likert scoring type, was applied; with a minimum score of 20 and maximum of 140, the level of empathy is directly related to the obtained score obtained. Results: One hundred resident physicians, 52% of them female, were surveyed. The mean score obtained was 112.88, with DE 14.51, median of 115, and a Cronbachs alpha coefficient of 0.82. The values of the quartiles were 102, 115 and 124. Twenty-six per cent of medical residents, 19.2% of surgery, 10% of gynecology-obstetrics and 35% of pediatrics reached higher values of the upper quartile. No statistically significant differences were found when comparing the respondents scores with each of the identified variables. Conclusions: Residents of the Pediatrics specialty has higher scores than the rest of the specialties, although no specific significant variables were found to explain the differences between the empathy levels.